MT-DRAGON score for outcome prediction in acute ischemic stroke treated by mechanical thrombectomy within 8 hours. (19th August 2019) - Ben Hassen, Wagih; Raynaud, Nicolas; Bricout, Nicolas; Boulouis, Gregoire; Legrand, Laurence; Ferrigno, Marc; Kazemi, Apolline; Bretzner, Martin; Soize, Sebastien; Farhat, Wassim; Seners, Pierre; Turc, Guillaume; et al.
Abstract : Objectives: The MRI-DRAGON score includes clinical and MRI parameters and demonstrates a high specificity in predicting 3 month outcome in patients with acute ischemic stroke (AIS) treated with intravenous tissue plasminogen activator (IV tPA). The aim of this study was to adapt this score to mechanical thrombectomy (MT) in a large multicenter cohort. Methods: Consecutive cases of AIS treated by MT between January 2015 and December 2017 from three stroke centers were reviewed (n=1077). We derived the MT-DRAGON score by keeping all variables of the MRI-DRAGON score (age, initial National Institutes of Health Stroke Scale score, glucose level, pre-stroke modified Rankin Scale (mRS) score, diffusion weighted imaging-Alberta Stroke Program Early CT score ≤5) and considering the following variables: time to groin puncture instead of onset to IV tPA time and occlusion site. Unfavorable 3 month outcome was defined as a mRS score >2. Score performance was evaluated by c statistics and an external validation was performed. Results: Among 679 included patients (derivation and validation cohorts, n=431 and 248, respectively), an unfavorable outcome was similar between the derivation (51.5%) and validation (58.1%, P=0.7) cohorts, and was significantly associated with all MT-DRAGON parameters in the multivariable analysis. The c statistics for unfavorable outcome prediction was 0.83 (95%CI 0.79 to 0.88) in the derivation and 0.8 (95%CI 0.75 to 0.86) in the validation cohort. All patients (n=55) with an MT-DRAGONscore ≥11 had an unfavorable outcome and 60/63 (95%) patients with an MT-DRAGON score ≤2 points had a favorable outcome. Conclusion: The MT-DRAGON score is a simple tool, combining admission clinical and radiological parameters that can reliably predict 3 month outcome after MT.